Do chromatin loops provide epigenetic gene expression states? - Deng, Wulan (2010)
Control of gene expression involves the concerted action of multiple regulatory elements some of which can act over large genomic distances. Physical interaction among these elements can lead to looping of the chromatin fiber. Although posttranslational modifications of chromatin are thought to play a role in the conveyance of epigenetic information, it is largely unknown whether higher order chromatin organization such as looping contributes to epigenetic memory. A related unresolved question is whether chromatin loops are the cause or the effect of transcriptional regulation. Recent work from diverse organisms suggests a memory function for long-range chromatin interactions. It is proposed that higher order folding of the chromatin fiber can serve to maintain active and repressed states of gene expression.